PERAN DAN STRATEGI PUBLIC RELATION DALAM PEMBENTUKAN CITRA PERGURUAN TINGGI PARIWISATA - Apit Buchori (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2019)
The ability to display a positive image for a university that is trustworthy is a necessity that cannot be bargained, given the competitive conditions faced by the world of higher education in Indonesia today are very competitive, not only local and regional even to the global level. One of the work units responsible for the formation of corporate image is public relations. STIPRAM in order to improve its image has carried out roles and several public relations strategies, including building internal and external communication. Internal communications such as employee relations, student relations, management and foundation relations while external communication such as relations with government, associations, L2 Dikti, collaboration with domestic and foreign universities, tourism industry, media relations, Corporate Social Responsibility ( CSR), Publications, exhibitions and road shows to several high school and vocational schools in edufair form to introduce STIPRAM even closer to prospective students.Keywords: Public Relation, Public Relation strategic, image